Saluran dan Bauran Pemasaran Produk Agribisnis di Peternakan Donba Enggar Kecamatan Pare Kabupaten Kediri: Saluran dan Bauran Pemasaran Produk Agribisnis di Peternakan Donba Enggar Kecamatan Pare Kabupaten Kediri - Aditiya Primadito, Moh Raihan; Setiyadi, Heru; Nurul Choirina, Vifi (JURNAL ILMIAH AGRINECA, 2025)
This study was conducted at Donba Enggar Farm, located in Pare District, from November to December 2024, with the aim of identifying the marketing channels and margins of agribusiness products at Donba Enggar Farm and analyzing the 4P marketing mix (product, place, price, promotion) using a qualitative descriptive method. This study aims to: (1) Identify the marketing channels and margins of agribusiness products implemented at Donba Enggar Farm, Pare District, Kediri Regency. (2) Analyze the marketing mix of agribusiness products at Donba Enggar Farm, Pare District, Kediri Regency. The data collection techniques used in this study are observation, interviews, and documentation study. This research employs a qualitative approach with a descriptive design. All agribusiness product channels at Donba Enggar Farm, including sheep and feed products, can be considered efficient because they have a farmer's share value of more than 40%. The marketing mix for Donba Enggar's livestock products—namely sheep and feed—includes the use of elevated stalls (stilt pens) and modern pen management. This is supported by a strategic location with good availability of feed materials. The prices set by Donba Enggar for each product generally follow market prices, except for the feed products, which are produced in-house by the farm.